Kompetensi Guru Berbasis Psikologi Organisasi dalam Meningkatkan Kinerja Guru di PAUD : Penelitian - Arista cahyaningsih; Muhammad Zuhaery; Suyatno Suyatno (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Teacher competence plays a crucial role in improving the quality of education and schools. Therefore, a supportive work environment is essential for its development, leading to improved performance and quality. Teacher competence development is influenced by the organizational psychology of the workplace, which requires optimal implementation and cooperation from all school members. Organizational psychology significantly impacts teacher performance and maximizes results. This study employed qualitative methods with non-test instruments, including in-depth interviews and observations, to understand teachers' perspectives and experiences regarding organizational psychology-based competency development in improving performance in early childhood education (PAUD). The results indicate that a conducive work environment that pays attention to organizational psychology provides a strong foundation for teacher competency development, thereby improving performance, loyalty, and optimizing all aspects of teacher competency.